Getting freight trains back on track–How railway undertakings, infrastructure owners and regulators can navigate the main dilemmas in freight business to drive sustainable growth - Demiridis, Nikolaos; Pyrgidis, Christos (Frontiers in Sustainability, 2022)
Rail freight reportedly makes for an environmentally friendly means of transport. It also has significant potential for making a lucrative business, a stark contrast to rail passenger transport. Yet in Europe rail freight has long been displaced over its road equivalent and grown at rates inferior to overall land goods freight. Sustainable, profitable rail freight operations depend not only on goods volume, travel distance and pricing, but further on other key aspects permeating goods transportation by rail. Our research demonstrates that the choice for railway undertakings, infrastructure owners, and regulators alike, is in practice a complex one as depending on many, often competing factors. In fact, the key questions usually raised v.a.v. rail freight operations may be summed up to the following: (a) Mixed passenger and freight train operation or dedicated train corridors? (b) Conventional or heavy axle loads for freight trains? (c) Unitized wagonload or integrated trainload services? (d) Dangerous goods land shipping by rail or road? (e) Autonomous or manned freight train operation? This paper aims to break down what is seemingly a hard-to-balance decision-making process for rail freight players. It aims to record and analyze the forces and dynamics behind the dilemmas above and is intended to: inform those partaking in the decision-making process; help them individually and collectively make more sound decisions regarding rail operations as a whole – including, in particular, strategic decisions regarding policy and/or investment; and, eventually, to enable them to craft and pursue viable, sustainable transport and business strategies. The research is underpinned by literature data review.